Implementation of Regional Regulation Number 16 of 2014 concerning the Arrangement and Empowerment of Street Vendors (PKL) on the Compliance Level of Business Actors in Grobogan Regency: Implementasi Perda Nomor 16 Tahun 2014 Tentang Penataan dan Pemberdayaan Pedagang Kaki Lima (PKL) Terhadap Tingkat Kepatuhan Para Pelaku Usaha di Kabupaten Grobogan - Amel Nurul Fadzilah Sidqi; Nadila Puspitasari (Indonesian State Law Review (ISLRev), 2022)
The existence of street vendors has opened up job opportunities so that the unemployment rate can be suppressed and its existence is needed by the lower class, because the prices are relatively cheaper than modern shops or restaurants. Street vendors always take advantage of places that are always seen as profit, for example the city center, crowded places to places that are considered to have the potential to become tourist attractions. On the one hand, the existence of street vendors is one of the safety valves to overcome unemployment as a whole, but on the other hand the phenomenon or growth of street vendors has resulted in the disruption of aspects of public order which are prerequisites for the ideal conditions of a city. To overcome these problems, the Grobogan Regency Government issued Regional Regulation (Perda) No. 16 of 2014 concerning the arrangement and empowerment of Street Vendors.The problem in this research is how the implementation of Regional Regulation Number 16 of 2014 concerning the Arrangement and Empowerment of Street Vendors on the Compliance Level of Business Actors in Grobogan Regency. The research method used is sociological juridical. The focus of the location is in Purwodadi City, Grobogan Regency. Research results Grobogan district government plays a role as enforcer of regional regulation no 16 of 2014 on the level of compliance of street vendors by providing guidance and direct action for the implementation of public order and city tidiness in Grobogan Regency. The research took place in June-July 2022 at the Grobogan district Satpol PP office. The role of the Grobogan district government in enforcing Regional Regulation No. 6 of 2014 has been going well. However, along the way, there are still some obstacles experienced by the government, namely there are still many naughty traders and the lack of supporting infrastructure for members of the Satpol PP.